Existence Results for A Perturbed Fourth-Order Equation - Heidari Tavani, Mohammad Reza (Journal of the Indonesian Mathematical Society, 2017)
‎The existence of at least three weak solutions for a class of perturbed‎‎fourth-order problems with a perturbed nonlinear term is investigated‎. ‎Our‎‎approach is based on variational methods and critical point theory‎.